Strategies and practical approaches for stable and high energy density sodium-ion battery: a step closer to commercialization - Yadav, P.; Patrike, A.; Wasnik, K.; Shelke, V.; Shelke, M. (Materials Today Sustainability, 2023)
Sodium-ion batteries (SIBs) are reckoned as a potential alternative to Li-ion batteries (LIBs). Currently, the limited supply of precursors and the cost of LIBs have regenerated research and development interest in SIBs. Due to differences in the chemistry of lithium (Li) and sodium (Na), optimized methods for LIBs cannot be blindly applied to develop SIBs. Along with the judicial selection of electrode materials, electrolytes, and interfaces are very crucial for safe, high-power, and long-lasting batteries. The initial part of this review deals with the challenges faced in commercializing SIB full cells. Subsequently, the strategies to improve the energy density of SIB full cells through electrode modifications and electrolyte engineering are described in detail. This review comprehensively represents notable insights into the large-scale commercialization of potential sodium-ion batteries in the full cell.(c) 2023 Elsevier Ltd. All rights reserved.
Keywords: Cathode additives; Electrolyte additives; Na compensation; Self -sacri ficial salts; Sodium -ion battery